Brain Games and Gymnastics on Increasing Concentration Power of Early Childhood - Dian Dian; Henie Hikmah Mediani; Minnatillah Minnatillah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to see the extent to which the level of concentration ability of early childhood after games and brain exercises are carried out in a period of 3 months. Brain games and exercises with simple body movements accompanied by songs to make students more excited. Brain exercise has many benefits, especially to balance the left and right brain, through brain exercise activities can foster enthusiasm and children's learning. This study describes brain exercise activities carried out at the Al-Kautsar Quran Kindergarten in Bandung. The method used is a descriptive approach. Data collection techniques are observation, interviews and documentation, while the data analysis technique is data triangulation technique. The results of research at Al-Kautsar Quran Kindergarten show that brain exercise activities have been carried out well, seen from semester and daily planning and evaluations carried out for each brain exercise activity. The implementation of this brain exercise provides many benefits for children to be more focused, improve memory and be more enthusiastic